Pengaruh Kinerja Keuangan, Leverage dan Strategi Bisnis Terhadap Penghindaran Pajak: Studi Pada Perusahaan Telekomunikasi Indonesia yang Terdaftar di BEI 2020-2023 - Theofani J.A. Roreng; Tri Siwi Nugrahani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Tax avoidance has become a major concern in corporate financial management, particularly in capital-intensive industries such as telecommunications. This study examines the influence of financial performance, leverage, and business strategy on tax avoidance among telecommunication companies listed on the Indonesia Stock Exchange during 2020–2023. A quantitative approach was employed using secondary data obtained from annual financial reports. The sample comprised 13 companies selected through a saturated sampling technique based on predetermined criteria. Data were analyzed using multiple linear regression following classical assumption testing, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The findings indicate that financial performance, leverage, and business strategy each have a significant effect on tax avoidance. Simultaneously, the three variables also exert a significant influence on corporate tax avoidance behavior. The correlation analysis demonstrates a moderate relationship between the independent variables and tax avoidance, while the coefficient of determination shows that financial performance, leverage, and business strategy explain 25.9% of the variation in tax avoidance, with the remainder attributable to other factors beyond the scope of this study. These findings highlight the importance of financial and strategic corporate decisions in shaping tax avoidance practices.